STATISTICAL OPTIMIZATION OF CULTIVATION CONDITIONS FOR SACCHAROMYCES BOULARDII VIA CENTRAL COMPOSITE DESIGN - Guowei Shu; Xin Yang; Li Chen; Dan Huang; Zhangteng Lei; He Chen (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Saccharomyces boulardii (S. boulardii) is used in many countries as both a preventive and therapeutic agent for diarrhea and other gastrointestinal disorders caused by the administration of antimicrobial agents. However, there are few reports on its culture conditions. Therefore, the aim of this study was to optimize the cultivation conditions of S. boulardii by single factor experiment and central composite design of Response Surface Methodology (RSM). The effects of temperature (28, 31, 34, 37, 41 °C), initial pH value (2, 4, 6, 8 and 10), liquid loading (25, 50, 75, 100 and 125 mL in 250 mL triangular flask), inoculum size (1, 3, 5, 7 and 9 %), and shaking speed (140, 160, 180, 200, 220 rot∙min-1) were investigated. Among these variables, the combination of 37 °C temperature, 6.4 the initial pH value, 250 mL triangular flask with 52 mL medium volume, 3 % inoculum size, and 181 rot∙min-1 shaking speed were found to be the most suitable cultivation conditions. Under the optimized conditions, the maximal yeast count was (1.81±0.06)×108 CFU∙mL-1, which was in a good agreement with the predicted value of the model. This study has provided useful information on how to improve the viable cells of yeast cells for S. boulardii culture.